Lénine et la science militaire - Tsvetkov, V.; Rybkine, E.; Dzuba, I. (Moscou : Editions du Progrès, 1967)
Bibliotheek François Vercammen
Vertaald uit het Russisch
Frans
Monografie
Keywords: Lenin, Vladimir